Cost reduction study of bicycle by using DFA methods - Ho, Ka Hui (2012)
Design for Assembly (DFA) is a tool for simplifying product design which enables to provide a good design to be easily manufactured and assembled. The objectives of this study are to evaluate and improve the design efficiency of a selected bicycle. The study was carried out through few processes which are disassembly of bicycle, assemble of bicycle parts and at the same time tabulate assembly time according to the methods used last but not the least, calculation of design efficiency by using the synthesis data. The good indication of design evaluation using DFA is able to reduce number of parts and simplify the assembly process. Design evaluation on bicycle was analysed by Boothroyd-Dewhurst DFA and Hitachi AEM methods. The evaluation result on existing efficiency design of bicycle shows 26.97 % by BD method and 69.83 % by Hitachi method. Furthermore the improvement designs also improve the assembly time. This result shows the DFA method was successfully applied to the selected bicycle.